Solve for p 3p-5(p+4)=-(p-7)

Math
3p-5(p+4)=-(p-7)
Simplify 3p-5(p+4).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3p-5p-5⋅4=-(p-7)
Multiply -5 by 4.
3p-5p-20=-(p-7)
3p-5p-20=-(p-7)
Subtract 5p from 3p.
-2p-20=-(p-7)
-2p-20=-(p-7)
Simplify -(p-7).
Tap for more steps…
Apply the distributive property.
-2p-20=-p–7
Multiply -1 by -7.
-2p-20=-p+7
-2p-20=-p+7
Move all terms containing p to the left side of the equation.
Tap for more steps…
Add p to both sides of the equation.
-2p-20+p=7
Add -2p and p.
-p-20=7
-p-20=7
Move all terms not containing p to the right side of the equation.
Tap for more steps…
Add 20 to both sides of the equation.
-p=7+20
Add 7 and 20.
-p=27
-p=27
Multiply each term in -p=27 by -1
Tap for more steps…
Multiply each term in -p=27 by -1.
(-p)⋅-1=27⋅-1
Multiply (-p)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1p=27⋅-1
Multiply p by 1.
p=27⋅-1
p=27⋅-1
Multiply 27 by -1.
p=-27
p=-27
Solve for p 3p-5(p+4)=-(p-7)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top